Pediatric Venous Thromboembolism: Different Rates of Incidence, Anatomic Locations, and Risk Factors Between Orthopaedic and Nonorthopaedic Related Patients. Issue 6 (1st July 2021) - Samineni, Aneesh V.; Sanborn, Ryan; Shea, Jodie; Cook, Danielle; May, Collin J.; Heyworth, Benton E.; Shore, Benjamin J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The prevalence of venous thromboembolism (VTE) may be increasing in children; however, scarce literature exists comparing incidence rates between pediatric orthopaedic patients and other pediatric patients. The purpose of this study was to compare the incidence, anatomic locations, and risk factors of VTEs between orthopaedic and nonorthopaedic pediatric related patients to determine if important differences exist. Methods: Computed tomography and ultrasound data were reviewed for children (below 19 y old) with a diagnosed VTE between January 1, 2009 and December 31, 2016. Demographic and clinical data, including VTE anatomic location and risk factors, were recorded. Two major cohorts were identified: orthopaedic-related (ORTH) and nonorthopaedic-related (NORTH) VTEs. Incidence rates were estimated and risk factors were compared using χ 2 testing. Results: There were 373 children diagnosed with a VTE (average age 10.3 y) of a total of 810, 097 treated as in-patients for an incidence rate of 4.60 per 10, 000 cases (95% confidence interval=4.15 to 5.10 per 10, 000 cases). The rate of ORTH VTEs (28 of 188, 669 orthopaedic patients, 1.48 per 10, 000 cases) was significantly lower than that of NORTH VTEs (345 of 621, 428 nonorthopaedic patients, 5.55 per 10, 000 cases; P <0.001). For the ORTH cohort, there was a significant difference in the proportion of deep vein thrombosis in the lower extremity (91%) compared with the upper extremity (9%) ( P <0.001), while a more even distribution of NORTH deep vein thrombosis in the upper (50%) and lower (41%) extremities was appreciated. The primary risk factors for ORTH VTEs included surgery (93%; P <0.001), change in ambulatory status (61%; P <0.001), and trauma (18%; P <0.001), while the primary risk factors for NORTH VTEs included intravenous peripheral inserted central catheter/central line (61%; P <0.001) and cancer (27%; P =0.001). Conclusions: Pediatric ORTH VTEs have a significantly lower incidence rate and different primary risk factors than those of NORTH VTEs. This information is useful for health care providers when making decisions regarding risk and prophylaxis in pediatric patients with orthopaedic and nonorthopaedic conditions. Level of Evidence: Level III.